Immune Phenomena in Myeloid Neoplasms: An “Egg or Chicken” Question - Barcellini, Wilma; Fattizzo, Bruno (Frontiers in Immunology, 2021)
Immune phenomena are increasingly reported in myeloid neoplasms, and include autoimmune cytopenias/diseases and immunodeficiency, either preceding or complicating acute myeloid leukemia, myelodysplastic syndromes (MDS), chronic myeloproliferative neoplasms, and bone marrow failure (BMF) syndromes. Autoimmunity and immunodeficiency are the two faces of a dysregulated immune tolerance and surveillance and may result, along with contributing environmental and genetic factors, in an increased incidence of both tumors and infections. The latter may fuel both autoimmunity and immune activation, triggering a vicious circle among infections, tumors and autoimmune phenomena. Additionally, alterations of the microbiota and of mesenchymal stem cells (MSCs) pinpoint to the importance of a permissive or hostile microenvironment for tumor growth. Finally, several therapies of myeloid neoplasms are aimed at increasing host immunity against the tumor, but at the price of increased autoimmune phenomena. In this review we will examine the epidemiological association of myeloid neoplasms with autoimmune diseases and immunodeficiencies, and the pivotal role of autoimmunity in the pathogenesis of MDS and BMF syndromes, including the paroxysmal nocturnal hemoglobinuria conundrum. Furthermore, we will briefly examine autoimmune complications following therapy of myeloid neoplasms, as well as the role of MSCs and microbiota in these settings.